Forensic accounting and Islamic behavioural insight on fund misuse in 1:87 diecast hobby - Fuad Yanuar Akhmad Rifai; Anis Chariri; Abdul Ghofur (Journal of Islamic Accounting and Finance Research, 2025)
Purpose - This study aims to explore the potential for fund misappropriation within the 1:87 diecast collector community using a forensic accounting approach integrated with Islamic behavioural accounting principles. Method - Employing a qualitative case study method, data were collected through in-depth interviews and documentation involving active collectors. Result - The study reveals patterns of non-transparent spending, manipulation of personal financial records, and rationalisation of consumptive behaviours that conflict with Sharia principles such as sidq (truthfulness) and amanah (trustworthiness). Implication - The integration of forensic accounting with Islamic behavioural values offers a corrective approach to personal financial management based on Sharia ethics. Originality - This research is among the first to address hobby-related consumption behaviour through the combined lens of forensic accounting and Islamic financial ethics.